2015
DOI: 10.1111/bjh.13323
|View full text |Cite|
|
Sign up to set email alerts
|

Pevonedistat (MLN4924), a First‐in‐Class NEDD8‐activating enzyme inhibitor, in patients with acute myeloid leukaemia and myelodysplastic syndromes: a phase 1 study

Abstract: SummaryThis trial was conducted to determine the dose-limiting toxicities (DLTs) and maximum tolerated dose (MTD) of the first in class NEDD8-activating enzyme (NAE) inhibitor, pevonedistat, and to investigate pevonedistat pharmacokinetics and pharmacodynamics in patients with acute myeloid leukaemia (AML) and myelodysplastic syndromes (MDS). Pevonedistat was administered via a 60-min intravenous infusion on days 1, 3 and 5 (schedule A, n = 27), or days 1, 4, 8 and 11 (schedule B, n = 26) every 21-days. Dose e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
207
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(214 citation statements)
references
References 49 publications
(73 reference statements)
7
207
0
Order By: Relevance
“…Indeed, MLN4924 has successfully passed through preclinical tests and is under evaluation for clinical stages. 36,37 A phase 1 study has been done on patients with acute myeloid leukemia and myelodysplastic syndromes. The patients were treated with a 60-min intravenous infusion of MLN4924 according to two different administration schedules, which were repeated every 21 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, MLN4924 has successfully passed through preclinical tests and is under evaluation for clinical stages. 36,37 A phase 1 study has been done on patients with acute myeloid leukemia and myelodysplastic syndromes. The patients were treated with a 60-min intravenous infusion of MLN4924 according to two different administration schedules, which were repeated every 21 days.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the patients' responses, the maximum tolerated dose (MTD) of MLN4924 was finally determined as either 59 or 83 mg/m 2 in two cohorts. 37 However, as MLN4924 has been tested as an anticancer drug, the tolerable upper limit of toxicity may be higher than that of developing anti-obesity drugs. This is why we treated mice with MLN4924 at a lower dose.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary reports from a Phase I clinical trial of MLN4924 in AML have indicated benefit in patients with difficult to treat relapsed and refractory disease. 4 As clinical development of MLN4924 in myeloid malignancies continues (www.clinicaltrials.gov), these promising results provide the impetus for determining the mechanism of MLN4924-induced cytotoxicity downstream of NAE inhibition, understanding possible mechanisms of MLN4924 resistance in AML, and assessing possible strategies for combining MLN4924 with other agents that have activity in hematological malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…36 Pevonedistat has been evaluated in patients with relapsed/refractory AML or myelodysplastic syndrome. 37 Two dose schedules were tested among 53 patients: pevonedistat was administered at escalating doses For personal use only. on May 12, 2018.…”
Section: Discussionmentioning
confidence: 99%